New ESC-ESH Guidelines on Arterial Hypertension - Anthony Heagerty (Heart Research, 2007)
Austria, Vienna, Sunday 2 September 2007: In 2000, 26% (972million) of the adult population worldwide had hypertension and this figure is estimated to rise by 2025 to 1.56billion. Such individuals have an increased risk of stroke or heart disease and the detection and effective management of such patients presents an enormous challenge to healthcare systems. Identifying specific patients at risk of developing organ damage will allow better deployment of preventative healthcare resources. Against this background, the European Society of Cardiology and the European Society of Hypertension have revised their 2003 guidelines based upon the publication of new evidence. The cornerstone of treatment remains the introduction of lifestyle measures such as increasing exercise, reducing body weight and other environmental factors such as reducing the intake of alcohol and salt before embarking on a treatment programme involving drugs.